Code Enforcement Of Sanctions For Notary Who Having Multiple Offices - Abiem Pandya Prasojo; Anis Mashdurohatun; Ngadino Ngadino (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
In every office attached to someone will be accompanied by moral rules called code of ethics as well as the notary office. Code of conduct notary entire moral code is determined by the association organization